The effect of winding patterns on the mechanical behavior of filament-wound cylinder shells. Issue 3 (13th November 2019) - Guo, Zhangxin; Li, Zhonggui; Cui, Junjie; Li, Yongcun; Luan, Yunbo
Abstract : Purpose: The purpose of this paper is to present a finite element analysis (FEA) of filament-wound composites, as well as application of these materials. Design/methodology/approach: In this paper, a new finite element method of filament-wound composite is presented. The stress and strain fields in the composite cylinders are analyzed using the ABAQUS software packages for considering the filament undulation and crossover. The paper presented results of buckling load of composite cylinders with different types of filament-winding patterns. Findings: The result of the example shows that the stress distributions are uniform along the cylinder length and around the circumference when the analytical approach is based on the conventional FEA. The stress distributions are not uniform along the cylinder length and around the circumference for considering the filament undulation and crossover. The stress units are arranged in a regular geometric pattern around circumference and along the axis of rotation. The analysis of the effect of filament-winding mosaic patterns on the mechanical characteristics of composite cylindrical is presented in the paper. Originality/value: The stress and strain fields in the composite cylinders were analyzed for considering the filament undulation and crossover. The buckling load of composite cylinders with different types of filament-winding patterns was presented in this paper.